تفعيل مادة الدفاع عن السنة المطهرة في مواجهة تيارات الراديكالية وظاهرة الإسلاموفوبيا - Muhammad Khoirul Mustaghfirin (Al-Zahra : Journal for Islamic and Arabic Studies, 2023)
This research aims to answer one of the contemporary social and religious issues, which means the issue of the phenomenon of Islamophobia and radicalism trought in the field of the glorious sunnah and how to overcome it by activating the article of the defender of the sunnah. Make shift scientific responses, whether it is textual evidence from the text of the Holy Scripture and Holly Qur’an and Sunnah, or rational evidence from logic, origins, and language, which is considered one of the mechanisms and tools of legal science. especially books dealing with modern suspicions. The results achieved by the researcher, among others: The activation of the article "Defending the Sunnah" is considered one of the tools and mechanisms that a Muslim can use to deal with extremist groups and the phenomenon of Islamophobia. However, it must be in a scientific, logical, rational, persuasive and thoughtful manner, and in a way that corrects some of the distorted concepts, suspicious ideas and wrong opinions about this true religion.